Chondroitin 6-Sulfation Regulates Perineuronal Net Formation by Controlling the Stability of Aggrecan - Shinji Miyata; Hiroshi Kitagawa (Neural Plasticity)
Perineuronal nets (PNNs) are lattice-like extracellular matrix structures composed of chondroitin sulfate proteoglycans (CSPGs). The appearance of PNNs parallels the decline of neural plasticity, and disruption of PNNs reactivates neural plasticity in the adult brain. We previously reported that sulfation patterns of chondroitin sulfate (CS) chains on CSPGs influenced the formation of PNNs and neural plasticity. However, the mechanism of PNN formation regulated by CS sulfation remains unknown. Here we found that overexpression of chondroitin 6-sulfotransferase-1 (C6ST-1), which catalyzes 6-sulfation of CS chains, selectively decreased aggrecan, a major CSPG in PNNs, in the aged brain without affecting other PNN components. Both diffuse and PNN-associated aggrecans were reduced by overexpression of C6ST-1. C6ST-1 increased 6-sulfation in both the repeating disaccharide region and linkage region of CS chains. Overexpression of 6-sulfation primarily impaired accumulation of aggrecan in PNNs, whereas condensation of other PNN components was not affected. Finally, we found that increased 6-sulfation accelerated proteolysis of aggrecan by a disintegrin and metalloproteinase domain with thrombospondin motif (ADAMTS) protease. Taken together, our results indicate that sulfation patterns of CS chains on aggrecan influenced the stability of the CSPG, thereby regulating formation of PNNs and neural plasticity.